Googlism – Man’s New “Religion” in the Digital Age - Jasiński, Karol (Philosophy and Canon Law, 2023)
The aim of this paper is to present the main premises of googlism and to characterize the various ways of understanding it. The paper comprises two main parts: the first part presents the main elements of googlism (the doctrine, moral principles, the cult and the community), which makes it resemble a religion in its conventional meaning. However, it emphasizes that the similarity to a religion is only superficial since one crucial element is missing: the affirmation of a supernatural and personal Absolute and an existential, dynamic and holistic interpersonal relation between It and man. Sacralization and deification of a search engine can hardly be regarded as a constitutive element of a religion. The second part contains characteristics of googlism as a lay religion, with the sacrum reduced to natural aspects as a result of technology sacralization; a digital religion, that is, a technological space which favors the creation of new religious content and practice; the “new spirituality” of the man of the era of a digital revolution; and, finally, a “joke religion,” which is a parody of religious life.